2017
DOI: 10.1002/jbm.a.36212
|View full text |Cite
|
Sign up to set email alerts
|

Dual growth factor‐immobilized asymmetrically porous membrane for bone‐to‐tendon interface regeneration on rat patellar tendon avulsion model

Abstract: Insufficient repair of the bone-to-tendon interface (BTI) with structural/compositional gradients has been a significant challenge in orthopedics. In this study, dual growth factor (platelet-derived growth factor-BB [PDGF-BB] and bone morphogenetic protein-2 [BMP-2])-immobilized polycaprolactone (PCL)/Pluronic F127 asymmetrically porous membrane was fabricated to estimate its feasibility as a potential strategy for effective regeneration of BTI injury. The growth factors immobilized (via heparin-intermediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 66 publications
0
6
0
2
Order By: Relevance
“…However, single factor can not fully mimic the complex process of physiological events during the interface healing. To enhance the regeneration of tissues with heterogeneous cell types and matrix compositions, delivering multiple bioactive growth factors into the target region is essential [ 96 ]. For example, Kim et al fabricated platelet-derived growth factor-BB (PDGF-BB)/bone morphogenetic protein-2 (BMP-2)-immobilized membrane to facilitate interface healing in a rat patellar tendon avulsion model [ 96 ].…”
Section: Growth Factors As Biomimetic Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…However, single factor can not fully mimic the complex process of physiological events during the interface healing. To enhance the regeneration of tissues with heterogeneous cell types and matrix compositions, delivering multiple bioactive growth factors into the target region is essential [ 96 ]. For example, Kim et al fabricated platelet-derived growth factor-BB (PDGF-BB)/bone morphogenetic protein-2 (BMP-2)-immobilized membrane to facilitate interface healing in a rat patellar tendon avulsion model [ 96 ].…”
Section: Growth Factors As Biomimetic Strategymentioning
confidence: 99%
“…To enhance the regeneration of tissues with heterogeneous cell types and matrix compositions, delivering multiple bioactive growth factors into the target region is essential [ 96 ]. For example, Kim et al fabricated platelet-derived growth factor-BB (PDGF-BB)/bone morphogenetic protein-2 (BMP-2)-immobilized membrane to facilitate interface healing in a rat patellar tendon avulsion model [ 96 ]. The results demonstrated that delivery of single growth factor might be insufficient to reconstruct the tendon-to-bone interface with a multiphasic structure, whereas the delivery of both PDGF-BB and BMP-2 may provide a synergistic effect to generate a multiphasic structure similar to the native enthesis structure.…”
Section: Growth Factors As Biomimetic Strategymentioning
confidence: 99%
“…It is well known that PDGF-BB enhances proliferation of fibroblasts [17][18][19]. In addition, PDGF-BB acts via chemotaxis and has an influence on the cell migration.…”
Section: Proliferation and Migrationmentioning
confidence: 99%
“…Bayer с соавторами рассматривают различные варианты доставки микросферами фактора роста и морфогенетического белка [4]. следует отметить, что применение pdgF в трав-матологической практике является перспектив-ным направлением, и в настоящее время в мире идет активный поиск способов доставки, сро-ков и длительности эффективного применения pdgF для ускорения костной регенерации [3][4][5]. недавно корейскими учеными было доказано ускорение регенерации при использовании мик-росфер с ассиметричными порами в мембранах, которые высвобождали pdgF-ВВ и ВМР-2 [5].…”
unclassified
“…следует отметить, что применение pdgF в трав-матологической практике является перспектив-ным направлением, и в настоящее время в мире идет активный поиск способов доставки, сро-ков и длительности эффективного применения pdgF для ускорения костной регенерации [3][4][5]. недавно корейскими учеными было доказано ускорение регенерации при использовании мик-росфер с ассиметричными порами в мембранах, которые высвобождали pdgF-ВВ и ВМР-2 [5]. по данным других авторов, проводивших исследова-ние на животных, использование тромбоцитар-ного и эндотелиального (VegF) факторов роста сосудов в комбинации с ВМР-2 более эффективно для костной регенерации по сравнению с моноте-рапией ВМР-2 [6].…”
unclassified